Filipinos bilib kay albularyo: Its implications on one’s faith-life - Cabatbat, Katherine Pia M. (Animo Repository, 2017)
Filipinos are naturally inclined to animism. This inclination leads some of them to depend their health problems to something spiritual and cultural. When the health of a family member is at-risk, the urban poor seek traditional healing (Salenga, 2012). The researchers seek to enumerate the motivational factors that led the urban poor families to avail the services from the traditional healers specifically the albularyos. Likewise, this study identified the significance of these motivational factors in the exercise of their faith. This study employed qualitative method of research and utilized the focused-group discussion. Using purposive sampling method, the researchers convened 10 individuals from the urban poor in Manila particularly in Brgy. 719, Leveriza St., Malate Manila who sought healing and were healed by the so called albularyos. This barangay is situated at the heart of the city near Philippine General Hospital (PGH), the biggest government-owned and controlled hospital in the country. Based from the study conducted, Filipinos believed in the supernatural power of the albularyo. This created Juan’s mindset of a positive outlook in life which led to their wellbeingness and deepened their faith- life. They also consider that the albularyo is a divine instrument whom God sent to make them well.